Elliptic Cylinder with Slotted Antenna Coated with Magnetic Metamaterials - A. K. Hamid (International Journal of Antennas and Propagation)
The radiation properties of an axially slotted elliptic antenna coated with magnetic metamaterials are investigated. The fields inside and outside the dielectric coating are expressed in terms of the Mathieu functions. The boundary conditions at various surfaces are enforced using the orthogonality property of angular Mathieu functions. Numerical results are presented graphically for the radiation pattern, aperture conductance, and antenna gain for the TM case. It was found that a slotted antenna coated with magnetic metamaterials has more gain as well as lower side lobes compared to one coated with conventional dielectric or nonmagnetic metamaterials.